Gut microbiota in hypertension. Issue 5 (September 2015) - Jose, Pedro A.; Raj, Dominic
Abstract : Purpose of review: Hypertension, which is present in about one quarter of the world's population, is responsible for about 41% of the number one cause of death – cardiovascular disease. Not included in these statistics is the effect of sodium intake on blood pressure, even though an increase or a marked decrease in sodium intake can increase blood pressure. This review deals with the interaction of gut microbiota and the kidney with genetics and epigenetics in the regulation of blood pressure and salt sensitivity. Recent findings: The abundance of the gut microbes, Firmicutes and Bacteroidetes, is associated with increased blood pressure in several models of hypertension, including the spontaneously hypertensive and Dahl salt-sensitive rats. Decreasing gut microbiota by antibiotics can increase or decrease blood pressure that is influenced by genotype. The biological function of probiotics may also be a consequence of epigenetic modification, related, in part, to microRNA. Products of the fermentation of nutrients by gut microbiota can influence blood pressure by regulating expenditure of energy, intestinal metabolism of catecholamines, and gastrointestinal and renal ion transport, and thus, salt sensitivity. Summary: The beneficial or deleterious effect of gut microbiota on blood pressure is a consequence of several variables, including genetics, epigenetics, lifestyle, and intake of antibiotics. These variables may influence the ultimate level of blood pressure and control of hypertension.